Pengaruh Social Media Marketing dan Online Customer Review Terhadap Minat Pembelian Pada Marketplace Lazada (Survey pada masyarakat di Kabupaten Karawang) - Chintya Dessy Syafitri; Danny Ramdani (Jurnal Ilmiah Wahana Pendidikan, 2022)
This study aims to learn, analyze, and explain research's variables, significance of social media marketing and online customer review relationships of Lazada marketplace users as well as the significance of social media marketing and online customer review partial and simultaneous influence on customer's buying interest. The method used is a quantitative research method with descriptive and verificative approach. This study is using primary data attained directly via questionnaire that was shared with the respondents. Hair et al. formula were used in this study, as well as purposive sampling technique, which led researcher to 120 respondents. The Likert scale model and Path Analysis were used with the help of Method of Successive Interval (MSI), Microsoft Office, and SPSS version 22. The result shows that there is a strong significant relationship between Social Media Marketing and Online Customer Review. Both variables have a rather significant positive influence on buying interest. Keywords: Social Media Marketing, Online Customer Review, Buying Interest